Development of the TTF TPACK survey instrument - Jamieson-Proctor, R.; Albion, P.; Finger, G.; Cavanagh, Rob; Fitzgerald, R.; Bond, T.; Grimbek, P. (ACCE - Journal for the Australian Council for Computers in Education, 2013)
One of the major outcomes from the national Teaching Teachers for the Future (TTF) Project in 2011 was the development and statistical validation of a survey instrument to measure the Technological Pedagogical Content Knowledge (TPACK) of pre-service teachers as a result of the TTF intervention implemented across all Australian Education Institutions (HEI) delivering pre-service teacher education programs. The TTF project was positioned within the context of the emerging implementation of National Professional Standards for Teachers (AITSL, 2011) and focused specifically on the national curriculum areas of Mathematics, Science, English and History. The TTF TPACK Survey instrument developed for the TTF Project was informed by earlier work on the measurement of TPACK and ICT integration in classrooms (Albion, Jamieson-Proctor & Finger, 2010; Jamieson-Proctor & Finger, 2009; Jamieson-Proctor, Watson, Finger, Grimbeek & Burnett, 2007). The development of the instrument was guided by the TTF Research and Evaluation Working Group and incorporated additional items to extend the earlier developed TPACK Confidence Survey (TCS), in order to meet the particular needs of the TTF project. The data collected were subject to a battery of complementary analysis procedures using both the pre (N=12881) and post (N=5809) data. Four scales were investigated and confirmed as reliable: (1) Confidence - teacher items; (2) Usefulness - teacher items; (3) Confidence - student items; and (4) Usefulness - student items. This paper describes the theoretical framework and psychometric properties of the TTF TPACK Survey developed and administered in 2011.